Political Game-Changers: The Importance of Leaders for Newly Emerged Parties in Romania. Issue 3 (2021) - Gherghina, Sergiu; Grad, Marius
Abstract : Party leaders continue to be crucial players in politics. The theories of personalization and presidentialization of party politics reflect the centrality of leaders' roles. Little attention has been paid to the effects of leaders on the formation and development of newly emerged parties. This article aims to fill that gap by analyzing the effect of leaders on the formation, intra-party cohesion, and membership organization of three newly emerged Romanian parties between 2015 and 2019. The qualitative analysis uses content from primary (party documents and elite discourses) and secondary sources (media reports). The findings indicate that the leaders' approaches towards party formation and organization differ substantially across the examined parties and explain their cohesion and electoral appeal.